Hubungan Kekuatan Otot Tungkai dan Koordinasi Mata Kaki Dengan Kemampuan Passing Sepakbola Dengan Kaki Bagian Dalam Pada Siswa SMA Taman Siswa Oba - Pribadi, Mahatma Raison (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to determine 1) the relationship between leg muscle strength and the ability to pass football with the inside of the foot in SMA Taman Siswa Oba students, 2) the relationship between eye-foot coordination and the ability to pass football with the inside of the foot in SMA Taman Siswa Oba students, and 3) the relationship simultaneously between leg muscle strength and eye-foot coordination with the ability to pass football with the inside of the foot in SMA Taman Siswa Oba students. This study is a correlational study. The subjects of this study were 30 male students of SMA Taman Siswa Oba. The results of the study showed that: 1) the results of the data analysis obtained a calculated r value of 0.897> r table value of 0.361, with a significance value of 0.05, so there is a relationship between leg muscle strength and the ability to pass football with the inside of the foot in SMA Taman Siswa Oba students. 2) the results of the data analysis obtained a calculated r value of 0.801> r table value of 0.361, with a significance value of 0.05, so there is a relationship between eye-foot coordination and the ability to pass football with the inside of the foot in SMA Taman Siswa Oba students., and 3) the results of the data analysis obtained a calculated F value (57.583)> F table (3.35) with a significance of 0.05, so the results stated that there is a relationship together between leg muscle strength and eye-foot coordination with the ability to pass football with the inside of the foot in SMA Taman Siswa Oba students. The conclusion of this study is 1) there is a relationship between leg muscle strength and the ability to pass football with the inside of the foot in SMA Taman Siswa Oba students, 2) there is a relationship between eye-foot coordination and the ability to pass football with the inside of the foot in SMA Taman Siswa Oba students, and 3) there is a simultaneous relationship between leg muscle strength and eye-foot coordination with the ability to pass football with the inside of the foot in SMA Taman Siswa Oba students.